Government Health Expenditure, Regional Economic Capacity, and Childhood Stunting in Papua Province - Innur Alfisyah; Elsyan R Marlissa; Transna Putra Urip (Jurnal Studi Multidisiplin Ilmu, 2026)
Purpose: This study examines the trend of childhood stunting prevalence in Papua Province between 2022 and 2024 and tests the partial and simultaneous influence of government health expenditure and regional economic capacity, proxied by Gross Regional Domestic Product (GRDP) per capita, on stunting prevalence across nine regencies and municipalities. Methodology: A quantitative panel data design was applied to secondary data from Statistics Indonesia, the Ministry of Health, the Directorate General of Fiscal Balance, and regional financial reports, estimated through panel regression in EViews 12. Results: Stunting prevalence stayed largely stagnant and remained above the national average. Government health expenditure showed a negative but statistically insignificant relationship with stunting prevalence, while GRDP per capita showed a negative and statistically significant relationship. Jointly, both variables significantly predicted stunting prevalence, with an R squared of 0.362, meaning the model explains 36.2% of its variance.Conclusions: Regional economic capacity carries more weight in reducing stunting than health expenditure alone, indicating that fiscal allocation needs pairing with sustained regional economic growth to produce measurable nutritional gains.Limitations: The three year window, narrow set of two predictors, and nine regency sample constrain generalization. Contributions: The study extends human capital theory by showing that the payoff from health spending depends on the economic capacity surrounding it, offering practical direction for fiscal and economic policy in Indonesia’s most persistently underdeveloped province.